Dynamics of T follicular helper cells in patients with rheumatic diseases and subsequent antibody responses in a three‐dose immunization regimen of CoronaVac. Issue 1 (19th September 2022) - Zhou, Xingyu; Wang, Yifan; Huang, Bo; Feng, Ruiling; Zhou, Xinyao; Li, Chun; Zhang, Xia; Shao, Miao; Gan, Yuzhou; Jin, Yuebo; An, Yuan; Xiao, Xian; et al.
Abstract: Given increased acceptance of the CoronaVac, there is an unmet need to assess the safety and immunogenic changes of CoronaVac in patients with rheumatic diseases (RD). Here we comprehensively analysed humoral and cellular responses in patient with RD after a three‐dose immunization regimen of CoronaVac. RD patients with stable condition and/or low disease activity ( n  = 40) or healthy controls ( n  = 40) were assigned in a 1:1 ratio to receive CoronaVac (Sinovac). The prevalence of anti‐receptor binding domain (RBD) antibodies and neutralizing antibodies was similar between healthy control (HC) and RD patients after the second and the third vaccination. However, the titers of anti‐RBD IgG and neutralizing antibodies were significantly lower in RD patients compared to HCs ( p  < 0.05), which was associated with an impaired T follicular helper (Tfh) cell response. Among RD patients, those who generated an antibody response displayed a significantly higher Tfh cells compared to those who failed after the first and the second vaccination ( p  < 0.05). Interestingly, subjects with a negative serological response displayed a similar Tfh memory response to severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)‐derived peptides as their anti‐RBD IgG positive counterpart, and all (4/4) of the non‐responders in HCs, and 62.5% (5/8) of the non‐responders in patients with RD displayed a positive serological response following the third dose. No serious adverse events were observed. In conclusion, our findings support SARS‐CoV‐2 vaccination in patients with RD with stable and/or low disease activity. The impaired ability in generating vaccine‐specific antibodies in patients with RD was associated with a reduction in Tfh cells induction. The window of vaccination times still needs to be explored in future studies. Clinical trial registration: This trial was registered with ChiCTR2100049138. Abstract : The impaired ability in generating vaccine‐specific antibodies in patients with RD was associated with a reduction in Tfh cells induction.